The Genealogy of Digital Asceticism in the Vortex of the Attention Economy: The Dialectic of Technologies of the Self and Muraqabah - Achmad Zain Avicena; Muchammad Helmi Umam (Journal of Islamic Civilization, 2025)
This study examines the genealogy of “digital zuhud” as a response to the attention economy that exploits individual subjectivity in the contemporary digital ecosystem. The main focus of the study is directed at the dialectic between Michel Foucault's concept of technologies of the self and the practice of muraqabah in the tradition of Islamic spirituality. Using a descriptive-analytical qualitative design with a literature study approach, this study analyzes the primary texts Technologies of the Self and Al-Ri'ayah through a philosophical parallelism method. The findings show that muraqabah functions as a transcendent mechanism that builds spiritual resilience to counter neoliberal alienation and self-quantification. Digital zuhud is formulated as a reconstructive framework for hybrid subjectivity to maintain moral agency amid algorithmic control. This study contributes to enriching the Foucaultian discourse with Eastern spiritual dimensions, while bridging the gap between Western technological ethics and Islamic tradition. The practical implications include guidelines for designing technologies that support ethical self-care. Future research is recommended to conduct empirical testing to validate the effectiveness of digital zuhud on a broader user population.